An analytical model to predict the effect of localised defect on vibrations associated with ball bearing. (2nd February 2010) - Patil, M.S.; Mathew, Jose; Rajendrakumar, P.K.; Desai, Sandeep
An analytical model has been proposed for predicting the effect of a localised defect on the ball bearing vibrations. The contact force is calculated using the Hertzian contact deformation theory. A computer programme is developed to simulate the defect on the raceways with the results presented in the time domain and frequency domain. Instead of using periodically repeated impulse function for the impulse due to defect, the defect itself is modelled as a part of sinusoidal wave. The effect of the defect size and its location on the vibration is investigated. The model yields both the frequency and the acceleration of vibration components of the bearing. A comparison between the theoretical and the experimental results obtained for 6305 deep groove ball bearing is provided to show that this model can be used to predict the spectral components.